2023
DOI: 10.1038/s41368-023-00227-2
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as a promoting factor of T2D: current evidence and mechanisms

Abstract: Periodontitis is an infectious disease caused by an imbalance between the local microbiota and host immune response. Epidemiologically, periodontitis is closely related to the occurrence, development, and poor prognosis of T2D and is recognized as a potential risk factor for T2D. In recent years, increasing attention has been given to the role of the virulence factors produced by disorders of the subgingival microbiota in the pathological mechanism of T2D, including islet β-cell dysfunction and insulin resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 144 publications
0
9
0
Order By: Relevance
“…The chronic, repetitious discharge of periodontal microbes and their byproducts into the bloodstream causes inflammatory markers to circulate and hence create or exacerbate insulin resistance ( 87 91 ) and DM complications ( 92 , 93 ).…”
Section: Dm/hyperglycemiamentioning
confidence: 99%
See 1 more Smart Citation
“…The chronic, repetitious discharge of periodontal microbes and their byproducts into the bloodstream causes inflammatory markers to circulate and hence create or exacerbate insulin resistance ( 87 91 ) and DM complications ( 92 , 93 ).…”
Section: Dm/hyperglycemiamentioning
confidence: 99%
“…Periodontal treatment decreases levels of several inflammatory biomarkers, many of which in turn are risk factors for DM complications like atherosclerosis and myocardial infarction, such as c-reactive protein ( 134 ) interleukin-(IL)-1beta ( 91 ), IL-6 ( 91 ), tumor necrosis factor-alpha (TNF-alpha) ( 91 ). Statistically significant decreases in the concentration of the active inflammatory marker, c-reactive protein, from baseline to each 3-monthly visit up to 1 year upon extraction of terminally periodontally diseased teeth and scaling and root planing the remaining dentition are reported ( 134 ).…”
Section: Effects Of Periodontal Treatmentmentioning
confidence: 99%
“…Approximately 10% of adults worldwide were affected in its severe form (Bernabe et al, 2020), and there were over 42 million individuals affected by severe periodontitis in the United States in 2019 compared with 28.3 million in 1990 (Chen et al, 2021). Periodontal disease is a risk factor for systemic diseases such as diabetes, cardiovascular diseases and cancer (Nwizu et al, 2020;Sanz et al, 2020;Su et al, 2023). In 2018, periodontal disease caused an estimated loss of $154.06 billion in the United States, imposing a heavy medical burden (Botelho et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological investigations have revealed that systemically healthy subjects with CP often show altered parameters related to β‐cell function, such as elevated homeostasis model assessment (HOMA) β index (HOMA‐β) values 6 and hyperinsulinemia 7 . Data from animal experiments have shown that periodontitis‐derived toxic products can interfere with β‐cell function 5 and have adverse effects on the metabolism of peripheral insulin‐targeting tissues, such as visceral adipose tissue, liver, and skeletal muscle, 4,8–10 which is an important cause of hyperinsulinemia or/and insulin resistance (IR). Recent study has demonstrated that the toxic product lipopolysaccharide (LPS) secreted by periodontal pathogens, Porphyromonas gingivalis ( P. gingivalis ), can cause endotoxemia and promote insulin secretion, which leads to hyperinsulinemia, 11 but the precise mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%